Rapid and actionable nasal-swab screening supports antimicrobial stewardship in patients with pneumonia: a prospective study - Siyao Chen; Yuanyuan Xiao; Caixia Tan; Juan Zhou; Ting Liu; Sisi Zhang; Yiran Hu; Yang Liu; Ming Zheng; Letao Chen; Xinghui Gao; Yi-Wei Tang; et al. (Antimicrobial Resistance and Infection Control)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA) nasal screening by polymerase chain reaction (PCR) is a rapid diagnostic tool with a high negative predictive value for pneumonia caused by MRSA. MRSA remains an important emerging pathogen in China and at present, there is little published data on the effect of rapid MRSA test results on antibiotic utilization for pneumonia. Methods A total of 300 inpatients who met the criteria of pneumonia in a tertiary general hospital were randomly assigned to a notification group (NG, n = 150) or a control group (CG, n = 150). Nasal swabs were collected and tested with the Xpert SA Nasal Complete Test (Cepheid, Sunnyvale, CA) to determine MRSA colonization status. Attending clinicians were immediately informed of test results for patients in NG while results were not released to an attending physician in CG. Subsequently, relevant medical records were collected and analyzed. Results Patients in the NG received a shorter duration of antimicrobial therapy compared to the CG (5.66 vs. 7.87 days, P < 0.001). Fewer renal injuries (1.33% vs. 8%; P = 0.015), and lower costs of antimicrobial agents ($621.78 vs. $881.70; P = 0.013) were observed in NG patients compared to those in the CG. Further, this intervention did not increase the in-hospital mortality (12.67% vs. 16.67%, P = 0.327). Conclusions Rapid and actionable MRSA PCR screening using nasal swabs helped reduce unnecessary anti-MRSA treatment. Early management of antimicrobials not only reduced the duration of anti-MRSA drug exposure but also antimicrobial-related adverse events.